Transient Global Amnesia as the Sole Presentation of an Acute Stroke in the Left Cingulate Gyrus - Lawrence Chau; Antonio Liu (Case Reports in Neurological Medicine)
We discuss a patient who presented to our hospital with signs, symptoms, and clinical course consistent with transient global amnesia (TGA). Her hospital work-up was overall unremarkable except for the presence of a diffusion weighted imaging (DWI) abnormality on MRI suggestive of acute infarction in the left cingulate gyrus. Symptoms quickly resolved, and she was discharged home in stable condition. While the etiology of TGA remains controversial, in discussing this case and the current literature we hope to provide further data supporting the possibility of an underlying ischemic process, as well as help better illustrate the neurologic structures involved.